2018
DOI: 10.1016/s2352-4642(18)30020-8
|View full text |Cite
|
Sign up to set email alerts
|

Association and birth prevalence of microcephaly attributable to Zika virus infection among infants in Paraíba, Brazil, in 2015–16: a case-control study

Abstract: Centers for Disease Control and Prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 21 publications
(25 reference statements)
3
84
0
7
Order By: Relevance
“…Mlakar et al (2016) identified ZIKV in the brain tissue of a severe microcephalic stillbirth whose mother had been infected with ZIKV in Brazil. This report was one of first to propose the possibility of an association between ZIKV and microcephaly, which was later confirmed by case-control studies with Brazilian newborns (MERG Group 2016;Cordeiro et al 2016;Brasil et al 2016;Krow-Lucal et al 2018).…”
Section: Introductionsupporting
confidence: 53%
“…Mlakar et al (2016) identified ZIKV in the brain tissue of a severe microcephalic stillbirth whose mother had been infected with ZIKV in Brazil. This report was one of first to propose the possibility of an association between ZIKV and microcephaly, which was later confirmed by case-control studies with Brazilian newborns (MERG Group 2016;Cordeiro et al 2016;Brasil et al 2016;Krow-Lucal et al 2018).…”
Section: Introductionsupporting
confidence: 53%
“…Microcephaly is challenging to monitor accurately as an outcome because it is difficult to reliably measure head circumference in a newborn, it can be affected by inaccuracies in estimated gestational age, and it does not distinguish between a small head size related to underlying pathology and one that will subsequently exhibit typical brain development ( 3 ). The sensitivity analysis suggests that the number of infants with Zika-associated birth defects could be a modest overestimate.…”
Section: Conclusion and Commentsmentioning
confidence: 99%
“…Evidence strongly supports a link between ZIKV infection and observed neurological complications 11, 12…”
Section: Discussionmentioning
confidence: 85%